Efektivitas Pelaksanaan KHI Tentang Ikrar Talak Di Depan Pengadilan: (Studi Multi Kasus Ulama Salafiyah Cukir) - Misbahul Munir (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2020)
Basically, the right to drop the divorce is in the hands of the husband, but as the leader of the husband's household it is not justified to commit violence against the wife, especially in terms of the wife's mentality because according to Islamic Fiqh, if the husband has dropped the word talak against the wife, it is said that he has fallen divorce. In this study, the authors took the formulation of the problem, namely: How is the Islamic concept of talak pledge, what is the concept of KHI about the talak pledge and how is the view of the Cukir ulama about the application of the talak pledge in front of the religious court. in front of a religious court or outside a religious court hearing, as well as their opinion on the imposition of divorce according to KHI. In order for this research to run in accordance with the objectives expected by the researcher, in this study the researcher used a qualitative approach with the type of field research research. Based on the available data, it can be analyzed that the Cukir ulama still adhere to classical fiqh, they do not agree with the obligation to pledge divorce in front of a religious court, they argue that divorce can fall anywhere without having to be in front of a religious court. The conclusion of this research is that according to the ulama Cukir talak it can fall anywhere, they take this opinion based on the alquran, classical fiqh, as well as their thoughts, experiences and knowledge.